Capacity-Building Training on Website Development for SMA 58 Jakarta Students Using HTML and JavaScript Programming Languages - Fauziah, Fauziah; Ningsih, Sari; Hayati, Nur; Andrianingsih, Andrianingsih; Shalihati, Ira Diana; Riyantoro Riyantoro; Indra Lukmana; Syaiful Syaiful; Muhammad Nurdin; Wijanarko, Sigit (Lembaga Pengembangan Kinerja Dosen, 2025)
Hyper Text Markup Language (HTML) is a markup language used to structure and format text documents through the use of tags that control the appearance of content on web pages. HTML defines various document elements such as headings, paragraphs, images, and lists, which form the basic structure of a webpage. JavaScript, on the other hand, serves as a programming language that adds interactivity and dynamics to web pages. While HTML provides the basic framework for website layout, JavaScript enhances functionality with features that cannot be achieved through HTML alone, such as dynamically manipulating elements and responding to user interactions. Together, these two languages form the core foundation for web development. This program aims to equip students of SMAN 58 with the skills to practice using HTML tags, understand the basics of JavaScript programming, and develop interactive web pages through online simulations. The training will be conducted in stages, beginning with the submission of a proposal to the school and followed by the scheduled training in June 2024. Students will use the One Compiler platform for real-time practice, allowing them to write and execute HTML and JavaScript code directly in the browser. The training will be conducted interactively, introducing the fundamental concepts of HTML and JavaScript, along with demonstrations showing how to create dynamic websites. In the final phase, students will take a quiz designed to assess their understanding of the material and their ability to apply the knowledge gained. Through this program, it is expected that students will master the basic skills of website creation and have the ability to independently develop their own interactive web projects. Additionally, this program aims to enhance students' digital awareness and technical skills in the era of information technology.